2D PbS Nanosheets with Zigzag Edges for Efficient CO2 Photoconversion. Issue 60 (30th September 2020) - Zhu, Zezhou; Qu, Yunteng; Wang, Zhiyuan; Zhou, Fangyao; Zhao, Changming; Lin, Yue; Li, Liqiang; Yao, Yagang; Wu, Yuen
Abstract: The rational design of transition‐metal sulfide with two‐dimensional (2D) structure and tunable edges on the nanoscale can effectively improve their activity for variously catalytic reactions. Herein, the 2D PbS nanosheets with abundant zigzag edges (e‐PbS NS), which exhibited an excellent performance for CO2 photoconversion to CO, were constructed. The zigzag edges on the PbS NS are beneficial for exposing more active sites and promoting charge separation, thereby accelerating the kinetics process of CO2 photoreduction. This study provides a strategy to regulate structure with effective edge sites for the CO2 reduction. Abstract : Edge sites : An enhanced photochemical activity for CO2 reduction was achieved over abundant edges sites PbS nanosheets. This study provides a strategy to regulate structure with effective edge sites for the CO2 reduction.